QUALITY SERVICE IN IMPROVING THE PROFITABILITY OF EDUCATIONAL INSTITUTIONS BASED ON PESANTREN - Hasan Baharun; Adi Wibowo; Heny Mulyani; Rofikatul Maula (Jurnal Isema : Islamic Educational Management, 2021)
This study aims to understand and analyze the school's strategy in increasing institutional profitability through strengthening Quality Service at SMA Nurul Jadid Paiton, Probolinggo. This research uses a qualitative case study approach. The results show that SMA Nurul Jadid seeks to increase school profitability by continuously strengthening Quality Service through five things: Crost-Interest Curriculum, namely cross-interest subjects that exist in each specialization; Performance, namely prioritizing the appearance of all components of the institution; Improving the quality of human resources, namely forming good and religious characters for all students and teachers; Excellent Service, namely excellent service for all school components; Infrastructure, namely as the effectiveness of student learning. This study implies the importance of institutions strengthening Quality Service to impact the profitability of institutions.